Keywords to Recruit Spanish- and English-Speaking Participants: Evidence From an Online Postpartum Depression Randomized Controlled Trial - Barrera, Alinne Z; Kelman, Alex R; Muñoz, Ricardo F (JMIR Publications, 2014)
BackgroundOne of the advantages of Internet-based research is the ability to efficiently recruit large, diverse samples of international participants. Currently, there is a dearth of information on the behind-the-scenes process to setting up successful online recruitment tools. ObjectiveThe objective of the study was to examine the comparative impact of Spanish- and English-language keywords for a Google AdWords campaign to recruit pregnant women to an Internet intervention and to describe the characteristics of those who enrolled in the trial. MethodsSpanish- and English-language Google AdWords campaigns were created to advertise and recruit pregnant women to a Web-based randomized controlled trial for the prevention of postpartum depression, the Mothers and Babies/Mamás y Bebés Internet Project. Search engine users who clicked on the ads in response to keyword queries (eg, pregnancy, depression and pregnancy) were directed to the fully automated study website. Data on the performance of keywords associated with each Google ad reflect Web user queries from February 2009 to June 2012. Demographic information, self-reported depression symptom scores, major depressive episode status, and Internet use data were collected from enrolled participants before randomization in the intervention study. ResultsThe Google ads received high exposure (12,983,196 impressions) and interest (176,295 clicks) from a global sample of Web users; 6745 pregnant women consented to participate and 2575 completed enrollment in the intervention study. Keywords that were descriptive of pregnancy and distress or pregnancy and health resulted in higher consent and enrollment rates (ie, high-performing ads). In both languages, broad keywords (eg, pregnancy) had the highest exposure, more consented participants, and greatest cost per consent (up to US $25.77 per consent). The online ads recruited a predominantly Spanish-speaking sample from Latin America of Mestizo racial identity. The English-speaking sample was also diverse with most participants residing in regions of Asia and Africa. Spanish-speaking participants were significantly more likely to be of Latino ethnic background, not married, completed fewer years of formal education, and were more likely to have accessed the Internet for depression information (P<.001). ConclusionsThe Internet is an effective method for reaching an international sample of pregnant women interested in online interventions to manage changes in their mood during the perinatal period. To increase efficiency, Internet advertisements need to be monitored and tailored to reflect the target population's conceptualization of health issues being studied. Trial RegistrationClinicalTrials.gov NCT00816725; http://clinicaltrials.gov/show/NCT00816725 (Archived by WebCite at http://www.webcitation.org/6LumonjZP).